БОБУРНИНГ ДАВР ВА КЕЧМИШ ТАРИХИГА ДОИР ҚАРАШЛАРИ - Сулаймонов, И.И. (ILIM hám JÁMIYET, 2018)
The article is devoted to the analysis of the views of Babur of his time and the last era as well as the ideas of winners and losers. The researcher tries to study the problem of the concept of personality in the work ―Baburname‖.